2021
DOI: 10.3389/fimmu.2021.643206
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Immunology: Implications for Dairy Cattle

Abstract: The growing world population (7.8 billion) exerts an increased pressure on the cattle industry amongst others. Intensification and expansion of milk and beef production inevitably leads to increased risk of infectious disease spread and exacerbation. This indicates that improved understanding of cattle immune function is needed to provide optimal tools to combat the existing and future pathogens and improve food security. While dairy and beef cattle production is easily the world’s most important agricultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 181 publications
(214 reference statements)
0
49
0
4
Order By: Relevance
“…According to Vlasova and Saif ( 2021 ), the growing world population (7.8 billion) exerts an increased pressure on the cattle industry amongst others. High yielding dairy cattle and their calves are more vulnerable to various diseases leading to shorter life expectancy and reduced environmental fitness.…”
Section: Discussionmentioning
confidence: 99%
“…According to Vlasova and Saif ( 2021 ), the growing world population (7.8 billion) exerts an increased pressure on the cattle industry amongst others. High yielding dairy cattle and their calves are more vulnerable to various diseases leading to shorter life expectancy and reduced environmental fitness.…”
Section: Discussionmentioning
confidence: 99%
“…It is critical to understand the natural immune mechanisms that fight infection and how vaccination, biosafety, nutrition, livestock and management practices could be used to maintain and enhance immune protection ( 43 ). The sequence and structure of IgH constant genes in yak were similar to those in bovids ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dr. Ma found that the bovine DH gene of ultra-long CDR3H had a ‘YxYx’ feature, which also appeared in the ultra-long CDR3H sequence of yak ( 11 ). CDR3H was located in the center of the antigen binding site and plays a key role in determining the specificity and affinity of antibodies ( 43 ). DH gene was the main component of CDR3H and largely determines the length and AA composition of CDR3H.…”
Section: Discussionmentioning
confidence: 99%
“…The potent innate immune system activation is essential for the development of pathogen-specific adaptive immune responses (Mishra et al 2017). Further, an in-depth and complete understanding of the cattle's natural anti-infectious immunity is essential for the effective management of cattle herds (Ferluga et al 2020;Vlasova and Saif 2021). The arrival of new high-throughput D r a f t sequencing technologies has significantly improved our understanding of the cattle immune system (Meade 2015).…”
Section: Introductionmentioning
confidence: 99%